Analisis Pelaksanaan Pembelajaran Kimia Dalam Penggunaan Media Digital Pasca Pandemi Covid-19 di SMAN 2 Mataram - Yusma, Lalu Arju Aria; Muntari, Muntari; Ariani, Sunniarti (FKIP University of Mataram, 2024)
This research aims to determine the implementation of chemistry learning in the use of digital media and to find out the obstacles to implementing chemistry learning in the use of digital media after the Covid-19 pandemic at SMA Negeri 2 Mataram. The approach used by researchers is a descriptive qualitative approach, determining informants using a non-probability sampling technique, namely purposive sampling. The percentage of implementation of chemistry learning using digital media at SMAN 2 Mataram has been carried out well, reaching 80%, the results of the questionnaire used the Likert scale calculation method. Chemistry learning uses digital media which is carried out by teachers using WPS Office Power Point media (Microsoft Word and Microsoft Power Point) and LCD. Meanwhile, students actively utilize digital learning platforms, namely accessing learning videos from YouTube, looking for material references through Ruang Guru, and actively discussing via WhatsApp groups. An obstacle in the chemistry learning process using digital media for teachers at SMAN 2 Mataram is the lack of teacher mastery in the development and use of digital media. Meanwhile, the obstacle for students in using digital media in learning is the limited internet connection for students at school.